Fatores preditores da recuperação funcional associada à transferência de nervos intercostais para reinervação do tríceps em paralisias completas do plexo braquial - Flores, Leandro Pretto (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2016)
Objective To evaluate the predictors of functional recovery associated with the transfer of intercostal nerves (ICNs) to the branch innervating the long head of the triceps (BLHT).Methods A retrospective analysis of 14 patients with global brachial plexus palsy for whom the surgical planning included the transfer of 2 or 3 ICNs to the BLHT.Results The effective rate of functional recovery for elbow extension was 28%. Surgical timing, severity of the injury, and number of ICNs did not show significance for functional recovery. Patients who underwent ICN transfer for reanimation of elbow extension in combination with phrenic nerve (PN) transfer for reinnervation of elbow flexion, or shoulder stability, obtained poorer results regarding triceps recovery (p < 0.01).Conclusions Intercostal nerves are reliable donors for reinnervation of the triceps in global brachial plexus injuries. However, this technique should be avoided in patients in whom the PN has been transferred for elbow flexion or shoulder abduction.
Keywords: brachial plexus; brain plasticity; nerve transfer; triceps palsy